A Liberal Enchanted by Socialism? The Issue of Ownership in Neoliberal Doctrine of Ferdinand Zweig - Pluciński, Przemysław; Pietrzak, Małgorzata (Studia Historiae Oeconomicae, 2011)
Ferdinand Zweig, who seems to be forgotten today, was one of the most eminent representatives of the so-called "Cracow School," an influential circle of economists associated with the Jagiellonian University. Zweig, as one of the ardent defenders and advocates of the revival of liberalism, devoted part of his considerations to the 'nature' of one of the fundamental social institutions, standing in the centre of the liberal doctrine, namely, the category of ownership. The idea of ownership as a socio-economic problem is never suspended in a vacuum; thus, in order to consider its place in Zweig's thinking, we should refer to this author's fascination with the liberal doctrine and his attitude to socialism, and in more detailed considerations as to the motifs of the criticism of monopolisation of the capitalist economy, expectations related to the stock form of ownership, and finally, issues related to social structure should be addressed.